How Refinery Industry Waste (Spent Bleaching Clay/Earth) Related to the Energy Fuel Demand: A review - Intan Shafinaz, Abd Manaf; Gaanty Pragas, Maniam (2014)
Biodiesel is an extender for traditional petroleum diesel and can be defined when the color show slightly yellow, oily liquid with a slight aromatic odor and a bitter taste. Commonly used as fuel for stationary diesel engine like pump sets, other agricultural implements and also in the diesel car. Realizing the importance of alternative energy sources, this research had come out with cost effective and versatile method for biodiesel preparation. In this research, the raw material feedstock had been taken from the refinery palm oil waste called spent bleaching clay. Refinery industry waste usually was dumped into landfill and cause environmental problems. This waste called spent bleaching clay. It is about 20-40 wt. % oil remains in spending bleaching clay which are taken from palm oil refinery. The transesterify between the oil and methanol can convert the oil into an alternative to fossil diesel fuel. This review had lined up all the transesterification method, the conversion yield, catalyst and other applications. The prospective of refinery waste will cover the future of biodiesel using waste as cost effective feedstock.